2006
DOI: 10.1016/j.regpep.2006.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by endogenous and exogenous PACAP following stroke

Abstract: We investigated the effects of PACAP treatment, and endogenous PACAP deficiency, on infarct volume, neurological function, and the cerebrocortical transcriptional response in a mouse model of stroke, middle cerebral artery occlusion (MCAO). PACAP-38 administered i.v. or i.c. v. 1 h after MCAO significantly reduced infarct volume, and ameliorated functional motor deficits measured 24 h later in wild-type mice. Infarct volumes and neurological deficits (walking faults) were both greater in PACAP-deficient than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 78 publications
4
113
0
Order By: Relevance
“…Numerous studies have shown that it plays a crucial role not only during secretion and motility but in immunity and inflammation processes (Azuma et al 2008;Arranz et al 2008;Gomariz et al 2006). Increasing evidence suggests that PACAP-38 has protective effects in I/R models, like in global and focal cerebral ischemia, retinal ischemia, kidney warm ischemia model, cultured cardiomyocytes, and in small bowel transplantation (Atlasz et al 2007;Chen et al 2006;Ohtaki et al 2008;Racz et al 2008;Riera et al 2001;Shioda et al 1998Shioda et al , 2006Reglodi et al 2004;Ferencz et al 2009a). However, there is no data on the effect of endogenous PACAP-38 against warm mesenteric ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that it plays a crucial role not only during secretion and motility but in immunity and inflammation processes (Azuma et al 2008;Arranz et al 2008;Gomariz et al 2006). Increasing evidence suggests that PACAP-38 has protective effects in I/R models, like in global and focal cerebral ischemia, retinal ischemia, kidney warm ischemia model, cultured cardiomyocytes, and in small bowel transplantation (Atlasz et al 2007;Chen et al 2006;Ohtaki et al 2008;Racz et al 2008;Riera et al 2001;Shioda et al 1998Shioda et al , 2006Reglodi et al 2004;Ferencz et al 2009a). However, there is no data on the effect of endogenous PACAP-38 against warm mesenteric ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…A significant literature also implicates cAMP in a broad range of neuronal differentiation responses, including neuritogenesis, survival, regeneration, repair, and expression of genes encoding neuron-specific proteins, such as neurotransmitter biosynthetic enzymes, neuropeptides, receptors, and ion channels (Qiu et al, 2002), although the effects of first messengers that regulate cAMP generation in differentiating neurons have not been studied as extensively as receptor tyrosine kinase-stimulating neurotrophins such as NGF. The neuropeptide PACAP has garnered significant interest in this regard, because PACAP is neuritogenic upon exposure to PC12 cells (Deutsch and Sun, 1992), enhances neuronal survival of cerebellar granule cells (Kienlen Campard et al, 1997) and PC12 cells (Tanaka et al, 1996), and is neuroprotective after ischemic injury to the brain (Reglodi et al, 2000;Chen et al, 2006;Ohtaki et al, 2006). PACAP signaling in PC12 cells leading to neuritogenesis is distinct from that of NGF.…”
mentioning
confidence: 99%
“…4(B)]. Whereas the IC50 for VIP(1 -7)/GRF (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), an established human VPAC1-specific agonist, at human VPAC2 was over 20 mM. These results showed that DBAYL could competitively displace […”
Section: Dbay L Selectively Binding To Vpac2 Receptormentioning
confidence: 99%
“…VPAC1 and VPAC2 receptors exhibit similar high affinity for PACAP38, PACAP27, and VIP [5]. PACAP is widely distributed in the brain and peripheral organs, notably in the endocrine pancreas, gonads, respiratory, and urogenital tracts, which has been shown to have effects on many pathological states including Parkinson's disease [6], diabetes [7,8], ischemia [9], traumatic injury [10], immunological disorders [11,12], myeloma kidney injury, and so on [13]. Most of these neuroprotective actions of PACAP are mediated through the selective PAC1 receptor whereas the effects on peripheral organs often involve VPAC1 or VPAC2 receptor.…”
Section: Introductionmentioning
confidence: 99%